Saxitoxin Level Comparation in Bali Sardine (Sardinella Lemuru) in Bali Strait in Different Monsoons - Endang Yuli Herawati; Mohammad Mahmudi; Fani Fariedah; Ruly Isfatul Khasanah (Research Journal of Life Science, 2016)
Sardinella fish (Sardinella lemuru) is a species of important pelagic fish from the family of Clupeidae found in Bali Strait. The dynamic condition of Bali Strait makes it fertile which is identical with plankton blooming. The objective of this research was to understand the potential of saxitoxin in sardinella fish because of dinoflagellates consumption in Bali Strait. The research was conducted in Southeast Monsoon (June - August 2015) and Northwest Monsoon (December 2015 – February 2016). The method used was in situ plankton sampling, counting and ELISA test to determine the level of saxitoxin in the fish. Hydro-oceanographic parameters measured were temperatures, salinity, DO (dissolved oxygen), pH level, phosphate level, nitrate level and transparency. They showed average optimum value for phytoplankton growth especially during Southeast Monsoon which its temperature lower and the nutrients (phosphate nitrate) higher than the Northwest Monsoon. This condition caused high richness of phytoplankton in the water and followed with dinoflagellates richness so they accumulated in sardinella fish. It was supported by the analysis of the fish gastric which showed positive correlation between dinoflagellates richness in the water and the fish gastric. ELISA test also showed that saxitoxin level of fish caught in Southeast Monsoon was higher than the one caught in Northwest Monsoon even though the level of saxitoxin was still in the safe range (less than 80 μg STXeq. per 100 g) but the danger of saxitoxin accumulation should be watched out for.